Live body weight estimation using cannon bone length and other body linear measurements in Nigerian breeds of sheep - Mahmud, Muhammad Abdullahi; Shaba, Peter; Abdulsalam, Wosilat; Yisa, Helen Yarubi; Gana, James; Ndagi, Silas; Ndagimba, Ruth (Journal of Advanced Veterinary and Animal Research, 2014)
The study was conducted in Mokwa, Nigeria, to estimate the live body weight (LBW) of Nigerian breeds of sheep using cannon bone length (CBL), and other linear body measurements (LBM). A total of 116 sheep were measured for LBW and LBM. The animals were categorized into two sex groups as male and female, and four age groups as <12 months, 13-24 months, 25-36 months and ?37 months. The current findings showed that in almost all the age groups, the chest depth and heart girth alone or in combination gave the best fitted prediction equation(s). However, the CBL negatively correlated with LBW in the male and female (combined) of <12 months age group, and positively correlated with LBW in the age groups of 25-36 and ?37 months. http://dx.doi.org/10.5455/javar.2014.a29